2022
DOI: 10.3389/fped.2022.969617
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status at age 1 year in patients born with esophageal atresia: A population-based, prospective cohort study

Abstract: ObjectiveDespite recent progress in caring for patients born with esophageal atresia (EA), undernutrition and stunting remain common. Our study objective was to assess nutritional status in the first year after birth with EA and to identify factors associated with growth failure.Study designWe conducted a population-based study of all infants born in France with EA between 2010 and 2016. Through the national EA register, we collected prenatal to 1 year follow-up data. We used body mass index and length-for-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…While the median height is close to normal during the first 6 months of life, growth decelerates thereafter in the sense that height crosses percentiles between the ages of 6 and 15 months and develops along the tenth centile of the general population until the age of 6 years. This finding corroborated the results of the French EA Registry, showing no catch-up growth during the first year of life, but a harmonious growth retardation in some patients at the age of one year [ 5 ]. Feeding problems seem to have an immediate impact in body weight, but a delayed impact on body height in patients with EA.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While the median height is close to normal during the first 6 months of life, growth decelerates thereafter in the sense that height crosses percentiles between the ages of 6 and 15 months and develops along the tenth centile of the general population until the age of 6 years. This finding corroborated the results of the French EA Registry, showing no catch-up growth during the first year of life, but a harmonious growth retardation in some patients at the age of one year [ 5 ]. Feeding problems seem to have an immediate impact in body weight, but a delayed impact on body height in patients with EA.…”
Section: Discussionsupporting
confidence: 89%
“…Feeding difficulties are multifactorial, including esophageal, oropharyngeal and behavioural disorders [ 3 ]. Furthermore, esophageal atresia is associated with other congenital malformations in over half of all cases [ 4 , 5 ], such as cardiac abnormalities (28 to 42% [ 4 , 5 ]), which may influence growth and development [ 2 ]. Low birth weight is also frequently associated: 17 % of children with EA are born small for gestational age [ 5 ] and around 40% of children are born preterm [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neither EA type nor surgical treatment was associated with growth failure. 13,14 Gastroesophageal reflux disease was addressed in a study that identified several predictive factors for surgery within the first year of life. These factors included gastroesophageal reflux disease, low birth weight, poor nutrition, and surgical anastomosis difficulties.…”
Section: Prenatal Diagnosismentioning
confidence: 99%